Endorectal sonography in rectal cancer staging and indication for local surgery - Vysloužil, Kamil; Ćwiertka, Karel; Zbořil, Pavel; Kučerová, Ladislava; Starý, Lubomír; Klementa, Ivo; Skalický, Pavel; Duda, Miloslav (Hepato-gastroenterology, 2007)
BACKGROUND/AIMS: Radical surgery still plays a decisive role in the therapy of rectal cancer. Besides classical abdominal operations, an alternative is transanal endoscopic resection of rectal tumor at T1 and T2 stages. Indication for local resection of malignant rectal tumor requires an accurate preoperative staging. METHODOLOGY: The paper evaluates the accuracy of 3D endorectal sonography in rectal cancer staging. In the group of 78 patients the staging of preoperative 3D endorectal sonography was compared with a final histopathologic of the operative sample. RESULTS: The results obtained indicate that the preoperative staging of malignant rectal tumor using 3D endorectal sonography represents 100% only in the pT1 stage. In the pT2 stage, the accuracy of 3D endorectal sonography is 72%, in pT3 and pT4 represents 92%. CONCLUSIONS: On the basis of our experience, complicated interpretation of findings obtained by 3D endorectal sonography occurs at limits of T2-T3 and T3-T4. In these localizations the peripheral reactive fibrous and inflammatory sections in the vicinity of tumor tissue often involve even the next layer of rectal wall and leads to overevaluation of invasion depth at endorectal sonography of rectal cancer.
Keywords: financování organizované; Endosonography; Financing, Organized; Rectum; lidé; nádory rekta; Female; mužské pohlaví; prospektivní studie; Rectal Neoplasms; staging nádorů; Male; Prospective Studies; rektum; Neoplasm Staging; ženské pohlaví; endosonografie; Humans